Rapid molecular diagnosis of ALB gene variants prevents unnecessary interventions in familial dysalbuminemic hyperthyroxinemia - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2021)
Objectives: Familial dysalbuminemic hyperthyroxinemia (FDH) is an autosomal dominant condition caused by heterozygous gain-of-function mutations in the human ALB gene. Case presentation: We report, a three-year-old boy with FDH due to p.R242P (or p.R218P without signal peptide) mutation in the ALB gene with a phenotype characterized by extremely high serum total and free thyroxine concentrations. His parents had normal thyroid function tests (TFT), so the mutation detected in this patient is assumed de novo. Although the most frequent variant was p.R242H in Caucasians and p.R242P in Japanese, our patient had p.R242P variant. Conclusions: Early identification of FDH is fundamental to prevent unnecessary repeats of TFT with different methods. We encourage the ALB gene hot spot sequencing initially and indicate that this molecular diagnosis is a rapid and simple method to diagnose FDH in individuals with euthyroid hyperthyroxinemia.
Keywords: ALB gene; albumin; familial dysalbuminemic hyperthyroxinemia; hyperthyroxinemia; thyroid hormone resistance; DEFECTS